A new species of Eupatorus Burmeister, 1847 related to Eupatorus birmanicus Arrow, 1908 from southwestern China (Coleoptera: Scarabaeidae: Dynastinae) - Prandi, Massimo; Grossi, Paschoal C. (Zootaxa, 2021)
A new species belonging to genus Eupatorus Burmeister, 1847, Eupatorus pyros Prandi & Grossi, new species (Scarabaeidae: Dynastinae: Dynastini: Chalcosomina), from southwestern China is described and illustrated. The new species is close to E. birmanicus Arrow, 1908. A distribution map and an identification key for the Eupatorus siamensis species-group are provided.